(untitled) (Medico Legal Update, 2020)
Background: Disasters define as event everywhere in the world every day and have a significant impact on individuals, families, group and communities. Objectives: The aim of the study was to assessment the nurses’ knowledge, attitude and practice about preparedness of disaster management in emergency of Mosul teaching hospitals/Iraq Materials and Method: In a cross-sectional analysis. The questionnaire consists of (4) main sections: section one demographic date e.g: (age, sex, experience, education level, marital status, and hospitals). Section two included: (47) items related to level of knowledge among nurses about disaster preparedness. Section three consists of (11) elements concern attitude about disaster management. Section four related to practice of regarding disaster management. Results: indicated the finding of the study nurses’ knowledge, attitude and practice about preparedness of disaster management in emergency department of Mosul teaching hospitals are highly significant. Conclusion: Through the findings of the study concluded that the awareness or knowledge of nurses is high with a neutral level of attitude, also practice with respect to disaster preparedness was satisfactory.